ÖĞRETMEN ADAYLARININ TÜRKÇENİN YAŞADIĞI SORUNLARA YÖNELİK FARKINDALIKLARI VE ÖNERİLERİ (MEHMET AKİF ERSOY ÜNİVERSİTESİ ÖRNEĞİ). - Bağci, Hasan (Electronic Turkish Studies)
The main goal of both foreign language education and mother tongue education is develop individual's language skills (reading, listening, visual, reading, writing, speech and visual presentation). The mother tongue is carrier of emotions, thoughts, and culture that make up the strongest ties between the individual and society. In the echelon of primary education when base, love, and awareness of native language are formed teacher is the person who will furnish students with the love and sensitivity for mother tongue. At first Primary school teachers and other all teachers should develop and internalize this kind of sensitivity and awareness prior to graduation. This study has been completed through survey model in order to determine candidate teachers' awareness of, sensitivity for, and opinions and suggestions regarding their mother tongue. Research universe consists of students studying at Turkish Language Teaching Department, English language Teaching Department, Elementary Education Department, Elementary Education Program and Social Sciences Education Program, Faculty of Education at Mehmet Akif Ersoy University while research sample is composed of senior students studying at the same program. This study is limited with the answers given by senior students who Faculty of Education at Mehmet Akif Ersoy University in the relevant sections of the spring semester of 2010-2011 academic year consisting of an open ended questions in the questionnaire. Open-ended questions in the questionnaire have been analyzed through descriptive analysis method; and findings have been depicted quantitatively.